Resolution of Inheritance Disputes in Gayo Society through Mediation: Perspective of Welfare and Gender Justice - Bustami, Kasdim; Saleh, Fauzi; Nurdin, Ridwan (Faculty of Law, Universitas Pekalongan, 2024)
The resolution of inheritance disputes in the Gayo Lues community, where women are disadvantaged (discriminated against) or receive injustice in the distribution of inheritance, leads to conflicts, disputes, and hostility within the family, causing disharmony within the family, society, culture, and customs. As a result, women in the Gayo Lues community do not fully receive their inheritance rights. Dispute resolution outside the court is called alternative dispute resolution (ADR). This research was conducted in Gayo Lues Regency, using a descriptive qualitative approach. The policy and implementation of mediation in resolving inheritance disputes are carried out through family deliberation, as the goal of